MUTATIS MUTANDIS PENGGUNAAN UNDANG-UNDANG NOMOR 29 TAHUN 2007 DENGAN UNDANG-UNDANG NOMOR 5 TAHUN 1985 TERKAIT PEMINDAHAN IBUKOTA NEGARA KESATUAN REPUBLIK INDONESIA - Adi Purnomo Santoso (Universitas Nasional, 2020)
The capital in a country plays a very strategic role. This is because the capital in a country can be multifunctional in addition to its main function as the Central Government, which will greatly affect other fundamental sectors of law, politics, business and economy, as well as all centers that characterize the overall character of a country. Broadly speaking, it can be concluded that the picture of a country can be seen from how its capital is. The discourse conveyed by President Joko Widodo in his State Speech on August 16, 2019, to move the Capital of the Unitary State of the Republic of Indonesia from Jakarta to Kalimantan Island received mixed reactions from many parties both legally and politically, in this case the authors prioritize the analysis of differences (Mutatis Mutandis) the legal strategic that can be taken by the Government in this case President Joko Widodo is by revising the Law, namely Law Number 29 of 2007 concerning the Provincial Government of the Special Capital Region as the Capital of the Unitary State of the Republic of Indonesia or by Referendum in accordance with Law Number 5 of 1985 concerning Referendum in making a right decision.